How language-specific and cross-linguistic factors affect speech rhythm - Nafiseh Taghva; Shouvik Chaudhuri (Estudios de Fonética Experimental)
This study examined the durational aspects of speech rhythm in Bengali (L1) and English spoken by educated Bengali advanced English learners (L2) to represent the effect of language-specific and cross-linguistic factors on speech rhythm. Employing metrics such as rateSyl, ΔC, nPVI-C, nPVI-V, VarcoV, %V, and ΔPeakLn, the study revealed that L1 exhibited a faster tempo, shorter consonants, and longer vowels relative to consonants, while L2 speech demonstrated greater variability in consonant and vowel durations, which are language-specific factors of L1 being a syllable-timed language and L2 being a stress-timed language. However, sonority patterns between syllables seemed consistent across L1 and L2 suggesting the cross-linguistic impact of L1 on L2. Moreover, the results identified the proportion of vocalic intervals (%V) as the most effective metric for differentiating between L1 and L2 rhythms.